Optimizing haemodialysis outcomes: A pilot study on the effectiveness of multidisciplinary clinics in enhancing vascular access and improving patient outcomes - Boon Cheok Lai; Hui Boon Tay; Pei Shan Lee (Proceedings of Singapore Healthcare)
Background Patients with kidney failure face increased health risks during early haemodialysis due to physical and emotional challenges. Most patients begin haemodialysis using catheters, which increases mortality and complication risks. This study evaluates the impact of multidisciplinary clinics on vascular access and patient outcomes on haemodialysis. Objectives To compare the influence of multidisciplinary clinics with conventional clinics on the utilisation of definitive vascular access for haemodialysis. Methods This is a single-centre, retrospective cohort study included 145 patients newly started on haemodialysis. Patients were evaluated over a 12-month follow-up period (July 2018 to December 2020). The primary outcome was definitive vascular access for haemodialysis. Secondary outcomes included the frequencies of catheter-related bloodstream infections, intensive care unit admissions, and recurrent hospitalizations. Results The study analysed 53 and 92 participants in the multidisciplinary clinics and conventional groups, respectively. Although only 10% of patients started haemodialysis with definitive access, the multidisciplinary clinics group exhibited significantly higher utilisation of definitive vascular access after 6 months (OR = 2.44, 95% CI 1.16-5.26, p = .039). The multidisciplinary clinics group had lower risks of intensive care unit admission (OR 0.92, 95% CI 1.03-1.15, p = .026) and recurrent hospitalization (OR 0.13, 95% CI 2.06-26.68, p = .001). Although not statistically significant (OR 0.34, 95% CI 0.47-18.46, p = .709), the multidisciplinary clinics group had a lower incidence of catheter-related infections. Conclusions Multidisciplinary care significantly increases the use of definitive vascular access, reduces intensive care unit admissions, and hospitalization rates, demonstrating the effectiveness of comprehensive, coordinated care in managing patients on haemodialysis.